Differential Expression of microRNAs Correlates With the Severity of Experimental Autoimmune Cystitis - Kumar, Vijay; Kiran, Sonia; Shamran, Haidar A.; Singh, Udai P. (Frontiers in Immunology, 2021)
Interstitial cystitis (IC)/bladder pain syndrome (BPS) primarily affects women. It varies in its severity and currently has no effective treatment. The symptoms of IC include pelvic pain, urgency and frequency of urination, and discomfort or pain in the bladder and lower abdomen. The bladders of IC patients exhibit infiltration by immune cells, which lends credence to the hypothesis that immune mechanisms also play a role in the etiology and pathophysiology of IC. The Differentially expressed microRNAs (miRs) in immune cells may serve as crucial immunoregulators in the IC. Therefore, we sought to determine whether miRs might play a regulatory role in the progression and pathogenesis of IC, using experimental autoimmune cystitis (EAC) model. In the present study, we observed differential expression of a specific subset of miRs in iliac lymph nodes (ILNs) and urinary bladders (UB) of IC mice compared to that in control mice. Microarray analysis of 96 miRs from the bladder and 135 miRs from ILNs allowed us to identify 50 that exhibited at least a 1.5-fold greater difference in expression in EAC mice compared to control mice. Hierarchical cluster analysis of the microarray data was used to search available databases to predict molecular pathways with which the miRs might interact. Four miRs from each organ that exhibited altered expression in EAC mice and that were predicted to have roles in inflammation (miR-146a, -181, -1931, and -5112) were selected for further analysis by reverse transcription-polymerase chain reaction (RT-PCR). All were confirmed to be elevated in EAC mice. Histological inflammatory scores, systemic chemokines, and cytokines expressed by T helper type 1 (Th1) lymphocytes were also elevated in EAC mice as compared to control animals. We hypothesize that the mechanism of EAC induction might involve the modulation of specific miRs that increase local and systemic levels of chemokines and cytokines. The present study identifies novel miRs expressed in UB and ILNs that will allow us to highlight mechanisms of EAC pathogenesis and may provide potential biomarkers and/or serve as the basis of new therapies for the treatment of IC.